التأصيل النظري لمفهوم الجاهلية السياسية في الفكر السياسي الإسلامي - حامد، محمد حازم (جامعة تكريت - كلية العلوم السياسية, 2018)
The political ignorance is an integral concept in political Islamic thought, the research shows that concept is theoretical determination among legitimate assumptions and illustrate its conceptual roots and determinate its indication features, represented by Holy Quran and Honorable Prophet Traditions (Sunnah) described by the principle sources for the political and Islamic sources, from these two divine sources, the political thinkers has derived the concept of political and an endoscopy and analysis of, the study require to divide the thesis into two demand, the first is: the concept of political ignorance in Holy Quran and Honorable Prophet Traditions (Sunnah), the second demand: the conceptualization of the concept of political ignorance.
تعد الجاهلية السياسية مفهوما أصيلا في الفكر السياسي الإسلامي، ويظهر البحث أن لهذا المفهوم تأصيل نظري يبين منطلقاته الشرعية ويوضح جذوره الفكرية ويحدد معالمه الدلالية، متمثلا بالقرآن الكريم والسنة النبوية الشريفة بوصفهما المصدران الأساسيان للفكر السياسي الإسلامي، ومن هذين المصدرين الربانيين أستمد المفكرون السياسيون مفاهيمهم للجاهلية السياسية تنظيرا وتحليلا، وأقتضى العمل تقسيم البحث على مطلبين، الأول: مفهوم الجاهلية السياسية في القرآن الكريم والسنة النبوية الشريفة، المطلب الثاني: تنظير المفكرين السياسيين لمفهوم الجاهلية السياسية.
Keywords: الفكر السياسي الإسلامي -- التنظيمات الإسلامية -- الجاهلية السياسية -- الدراسات التأصيلية